Moexipril effects on lung function in patients with arterial hypertension and chronic obstructive pulmonary disease - N. V. Ivanova; V. I. Lazareva; G. N. Kovan’ko (Кардиоваскулярная терапия и профилактика, 2006)
Aim. Taking into account a theoretical possibility of pro- and anti-inflammatory ACE inhibitor effects, to study moexipril influence on broncho-pulmonary status in patients with arterial hypertension (AH) and chronic obstructive pulmonary disease (COPD); to assess moexipril antihypertensive effect. Material and methods. The study included 25 patients with Stage II essential AH, Risk 3-4, and moderate-to-severe COPD. The effects of adding moexipril to standard therapy were assessed. Lung function dynamics was measured by Valenta diagnostic system. Moexipril antihypertensive action was assessed by 24-hour blood pressure monitoring results. Results. Moexipril did not affect ventilation parameters in COPD patients. Therefore, COPD could not be a contraindication for its administration in AH patients. Conclusion. The study confirmed good moexipril antihypertensive activity. A tendency for ventilation parameters’ improvement during moexipril treatment was observed, but longer observation period is needed for any firm conclusions.